Empowering Disabled Citizens in Indonesia through Inclusive Budget Planning: Rights and Responsibilities - Tsaputra, Antoni; Pollard, Eban (Indonesian Journal of Disability Studies, 2024)
This paper explores the multifaceted expectations of Disability Inclusive Budgeting (DIB) among disabled people, emphasizing its significance beyond mere disability mainstreaming within development goals. Informants' insights reveal that DIB carries diverse meanings and potential impacts. Firstly, there is an anticipation that DIB can facilitate the integration of disability considerations across all government programs through appropriate budget allocations. Additionally, the study participants express a broader aspiration: they believe that DIB has the potential to empower them to fulfill their civic responsibilities by positioning them as active agents of development. This, in turn, would enable their meaningful contributions to state-led development initiatives.